AN ANALYSIS OF ILLOCUTIONARY ACTS USED IN THE NEW TESTAMENT OF THE BOOK OF EPHESIANS - Daeli, Yudistira; Sidabutar, Usman; Siahaan, Sahat Taruli (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This thesis discusses the Analysis of Illocutionary Acts contained in the book of Ephesians chapters 1-2. The purpose of this research is to classify the types and functions of illocutionary speech acts contained in the book of Ephesians. This research was conducted using descriptive qualitative method. The reseacher reads and understands the contents of the book of Ephesians chapters 1-2 to obtain data. The data collection instrument is observation. The data is obtained from the book of Ephesians. The researcher found 45 data in the book of Ephesians. The types and functions of illocutionary contained in the book of Ephesians are representatives consisting of stating 5 data, convincing 1 data, informing 22 data, and affirming 8 data. Directives consisting of praying 3 data. Expressive consists of praising 3 data and wishing 3 data. The benefits of this research for the state and nation, especially for students and English teachers are that this research can be used as a source of teaching pragmatics material, a source of students in learning more about illocutionary acts, and for further researchers, especially in pragmatic illocutionary acts that analyze one-way objects such as articles, bibles, and books.